Answer:
The equation of the circle is;
![\mleft(x-7\mright)^2+\mleft(y+1\mright)^2=16](https://img.qammunity.org/2023/formulas/mathematics/college/yfp0jb72mfpspy0oksfjpzfnsx6z1ekctc.png)
Step-by-step explanation:
Given that the circle has a diameter with endpoints located at (7,3) and (7,-5).
The diameter of the circle is the distance between the two points;
![\begin{gathered} d=\sqrt[]{(7-7)^2+(3--5)^2_{}} \\ d=\sqrt[]{(0)^2+(3+5)^2_{}} \\ d=\sqrt[]{64} \\ d=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m6bamfjiqa53wk83qcnatfrmeo72ujm7yp.png)
The radius of the circle is;
![\begin{gathered} r=(d)/(2)=(8)/(2) \\ r=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lp30k2tudplx3d05laswz0nbobarderp3a.png)
The center of the circle is at the midpoint of the line of the diameter.
![\begin{gathered} (h,k)=((7+7)/(2),(3-5)/(2)) \\ (h,k)=((14)/(2),(-2)/(2)) \\ (h,k)=(7,-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tmt5o0h91cufpnavo123zhbk80ykudylot.png)
Applying the equation of a circle;
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
Substituting the given values;
![\begin{gathered} (x-h)^2+(y-k)^2=r^2 \\ (x-7)^2+(y+1)^2=4^2 \\ (x-7)^2+(y+1)^2=16^{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e2lb0f1mjlhso0j0wtg2uj3sehr86ci7o5.png)
Therefore, the equation of the circle is;
![\mleft(x-7\mright)^2+\mleft(y+1\mright)^2=16](https://img.qammunity.org/2023/formulas/mathematics/college/yfp0jb72mfpspy0oksfjpzfnsx6z1ekctc.png)